Aryl Hydrocarbon Receptor Deficiency Alters Circadian and Metabolic Rhythmicity. (April 2017) - Jaeger, Cassie; Khazaal, Ali Q.; Xu, Canxin; Sun, Mingwei; Krager, Stacey L.; Tischkau, Shelley A.
PAS domain–containing proteins can act as environmental sensors that capture external stimuli to allow coordination of organismal physiology with the outside world. These proteins permit diverse ligand binding and heterodimeric partnership, allowing for varied combinations of PAS-dependent protein-protein interactions and promoting crosstalk among signaling pathways. Previous studies report crosstalk between circadian clock proteins and the aryl hydrocarbon receptor (AhR). Activated AhR forms a heterodimer with the circadian clock protein Bmal1 and thereby functionally inhibits CLOCK/Bmal1 activity. If physiological activation of AhR through naturally occurring, endogenous ligands inhibits clock function, it seems plausible to hypothesize that decreased AhR expression releases AhR-induced inhibition of circadian rhythms. Because both AhR and the clock are important regulators of glucose metabolism, it follows that decreased AhR will also alter metabolic function. To test this hypothesis, rhythms of behavior, metabolic outputs, and circadian and metabolic gene expression were measured in AhR-deficient mice. Genetic depletion of AhR enhanced behavioral responses to changes in the light-dark cycle, increased rhythmic amplitude of circadian clock genes in the liver, and altered rhythms of glucose and insulin. This study provides evidence of AhR-induced inhibition that influences circadian rhythm amplitude.